ANALYSIS OF FACTORS AFFECTING THE APPLICATION OF AUSTRALASIAN TRIAGE SCALE (ATS) IN EMERGENCY DEPARTEMENT NGUDI WALUYO WLINGI HOSPITAL - Mohammad Nur Firdaus; Setyowati Soeharto; Dewi Kartikawati Ningsih (Journal of Nursing Science Update (JNSU), 2018)
Indonesia doesn’t have a national standard for triage system which means implementation in each hospital can be different. Nurses have an important role in the application of triage. The Australasian Triage Scale method (ATS) is one of the triage system in the world used in some countries including Indonesia but it is very difficult to implementation in overcrowded emergency departement. Nurses ratio and unstandard triage room make the ATS standart times is difficult to achieve. The aim of this study was to analyze the various factors affecting Australasian Triage Scale (ATS) in emergency departement NgudiWaluyo Wlingi Hospital. We used quantitative research with cross sectional approach and the respondent are 28 nurses in Emergency Departement Ngudi Waluyo Wlingi Hospital. Univariate analysis is used toknow the description of each variable. Fisher test to determine the relationship between variables. Logistic regression analysis to determine the most dominant factor affecting the application of Australasian Triage Scale. Fisher test result show p-Value as follows: performance factor (leadership), p =0.028 < α = 0,05, client factor (waiting time) p = 0.011 < α = 0,05, equipment factor (triage documentation) p = 0,036 < α = 0,05, staff requirements factor (education) ) p = 0.013 <α = 0,05, staff requirements factor (training) p = 0.036 <α = 0,05 The result of logistic regression shows staff requirements factor (education) p = 0.019 < α = 0.05 with OR 0.059. In conclusion there is a significant affecting between performance leadership factor, waiting time factor, triage documentation factor,education factor, training factor on the application of ATS and education is a dominant factor to predict the accuracy of the application of ATS.